Transcatheter Aortic Valve Implantation for Severe Bicuspid Aortic Stenosis – 2 Years Follow up Experience From India - Kumar, Vijay; Sengottuvelu, G.; Singh, Vivudh P.; Rastogi, Vishal; Seth, Ashok (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study has analysed the experience of TAVR procedures done in India for Bicuspid aortic valve population. Background: Transcatheter aortic valve replacement (TAVR) is technically challenging in Bicuspid aortic valve (BAV) anatomy because of numerous morphological phenotypes and involves the younger population of aortic stenosis patients. Methods and Results: A seventy patients’ data follow up of two years was pooled and analysed. SEV and BEV were implanted based on certain anatomical preferences. The Bicuspid aortic valve cohort constituted 24.4 % of the total 287 TAVR cases. The mean age was 72 years. The procedural success rate was 98%. The mean pressure gradient ranged between 0-15 mmHg and aortic valve area was close to 2cm2. These haemodynamics were consistent at 2 years follow up and patients were doing well. (PPI) was required in 11.4% of the patients. No one had a disabling stroke. Significant PVL at 2 years was none. Valve degeneration and failure or infective endocarditis was not seen. Conclusion: TAVR in bicuspid aortic valve population had good procedural success rate. The haemodynamics achieved was good and maintained at two years, thus seems to be a promising futuristic therapy for the young. PPI and non-disabling stroke are however unacceptable and needs to be addressed.